Regeneracija pročistača čestica ispušnih plinova Dieselova motora - Zavada, Josip; Mavrin, Ivan (Promet - Traffic&Transportation, 2012)
The paper studies the regeneration possibilities of Dieselexhaust particle filters, as well as the resulting problems.The application of exhaust particle filters is more and morerequired, because of the increasingly severe limitations imposedon the exhaust emissions of the Diesel engine vehicles.They are particularly necessary on lorries and buses. The particlestrapped in filters increase the counterpressure in the exhaustgases and reduce the engine performance. The most suitablemethod for perfO!ming regeneration is to bum the combustibleparticles trapped in the filter.The temperature of the Diesel engine exhaust gases in thementioned vehicles is not high enough to ignite the particles.To reach the temperatures higher than 550°C, certain measureshave to be undertaken. There are efficient measures outsidethe engine or their combination with measures within theengine.The paper deals especially with measures undertaken outsidethe engine, such as heating the filter using a burner, electricheater or microwave energy, use of fuel additives or applicationof a catalyser.